Clinical and radiographic delineation of Bent Bone Dysplasia‐FGFR2 type or Bent Bone Dysplasia with Distinctive Clavicles and Angel‐shaped Phalanges. Issue 10 (30th May 2016) - Krakow, Deborah; Cohn, Daniel H.; Wilcox, William R.; Noh, Grace J.; Raffel, Leslie J.; Sarukhanov, Anna; Ivanova, Margarita H.; Danielpour, Moise; Grange, Dorothy K.; Elliott, Alison M.; Bernstein, Jonathan A.; Rimoin, David L.; et al.
Abstract : Bent Bone Dysplasia‐FGFR2 type is a relatively recently described bent bone phenotype with diagnostic clinical, radiographic, and molecular characteristics. Here we report on 11 individuals, including the original four patients plus seven new individuals with three longer‐term survivors. The prenatal phenotype included stillbirth, bending of the femora, and a high incidence of polyhydramnios, prematurity, and perinatal death in three of 11 patients in the series. The survivors presented with characteristic radiographic findings that were observed among those with lethality, including bent bones, distinctive (moustache‐shaped) small clavicles, angel‐shaped metacarpals and phalanges, poor mineralization of the calvarium, and craniosynostosis. Craniofacial abnormalities, hirsutism, hepatic abnormalities, and genitourinary abnormalities were noted as well. Longer‐term survivors all needed ventilator support. Heterozygosity for mutations in the gene that encodes Fibroblast Growth Factor Receptor 2 ( FGFR2 ) was identified in the nine individuals with available DNA. Description of these patients expands the prenatal and postnatal findings of Bent Bone Dysplasia–FGFR2 type and adds to the phenotypic spectrum among all FGFR2 disorders. © 2016 Wiley Periodicals, Inc.